Task Dependent Effects of Head Orientation on Perceived Gaze Direction - Balsdon, Tarryn; Clifford, Colin W. G. (Frontiers in Psychology, 2018)
The perception of gaze direction involves the integration of a number of sensory cues exterior to the eye-region. The orientation of the head is one such cue, which has an overall repulsive effect on the perceived direction of gaze. However, in a recent experiment, we found the measured effect of head orientation on perceived gaze direction differed within subjects, depending on whether a single- or two-interval task design was employed. This suggests a potential difference in the way the orientation of the head is integrated into the perception of gaze direction across tasks. Four experiments were conducted to investigate this difference. The first two experiments showed that the difference was not the result of some interaction between stimuli in the two-interval task, but rather, a difference between the types of judgement being made across tasks, where observers were making a directional (left/right) judgement in the single-interval task, and a non-directional (direct/indirect gaze) judgement in the two-interval task. A third experiment showed that this difference does not arise from observers utilising a non-directional cue to direct gaze (the circularity of the pupil/iris) in making their non-directional judgements. The fourth experiment showed no substantial differences in the duration of evidence accumulation and processing between judgements, suggesting that observers are not integrating different sensory information across tasks. Together these experiments show that the sensory information from head orientation is flexibly weighted in the perception of gaze direction, and that the purpose of the observer, in sampling gaze information, can influence the consequent perception of gaze direction.